Incomplete ovarian tissue removal in female dogs and cats - England, Gary C.W.; White, Rob (BMJ Publishing Group, 2016)
Incomplete ovariectomy (IO) is the unintentional partial or complete lack of removal of one or both ovaries during an ovariohysterectomy or ovariectomy procedure, and is often referred to as ‘ovarian remnant syndrome’. It usually has a clear clinical presentation, although there are a number of other conditions that may have similar presenting signs. In female cats and dogs these include: non-oestrous mounting behaviour, non-oestrous vulval discharge and, solely in bitches, sexual interest from males and iatrogenic pseudopregnancy. This article considers the causes, presentation, methods of diagnosis and management of IO in bitches and queens.